(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The study was undertaken to investigate the effects of Telakucha (Cocciniaindica) on blood glucose, serum total cholesterol, hematological parameters and body weight in alloxan induced diabetic rats. In this experiment 45 rats were selected for the trial purpose. The rats were divided into 3 equal groups, each containing 15 individuals (n=15) as follows: normal control (C) group, diabetic control (DC) group and diabetic treatment (DT) group. Diabetes was induced in diabetic control (DC) and diabetic treatment (DT) group with alloxan @ 200mg/kg body weight intraperitonially. Then diabetic treatment group (DT) was treated with 10% aqueous extract of Telakucha @500 mg/kg body weight. After 42 days of treatment, Telakucha extract reduced the amount of blood glucose significantly (P<0.001) in the group DT compared to DC from 32.03 ± 0.25 to 11.17 ± 0.08 mmol/L. Total cholesterol (TC) was also decreased significantly (P<0.001) in group DT compared to group DC from 121.85±0.27 to 112.42±0.14 mg/dL. In hematological study, DT group showed significant (P<0.001) increase in erythrocytes count and Hb (g%) content and decrease (P<0.001) in total leukocyte count after 42 days of treatment in contrast with DC group. The body weight was also increased significantly (P<0.001) in DT group. Based on present research it can be concluded that Telakucha (Cocciniaindica) can be used in the treatment of diabetes as an alternative to commercial medicine. Res. Agric., Livest. Fish.7(3): 431-438, December 2020